Ernest & Celestine : a trip to Gibberitia [videorecording (Blu-Ray)] (Shout! Factory, 2024)
Ernest and Celestine return in this delightful and joyous follow-up to their first Academy Awardʼ-nominated adventure, where the bear and mouse became the unlikeliest of friends. When Celestine accidentally breaks the beloved violin of her grouchy companion, they embark on a journey to Gibbertia, home to the only artist who can repair it as well as Ernest's family. But when the duo arrives, they are shocked to discover that all forms of music have been banned for many years and the land once known for its incredible musicians has fallen silent. It is up to Ernest and Celestine and their new friends, including a mysterious masked outlaw, to bring music and happiness back to the land of bears